Kecemasan Matematika Siswa Sekolah Menengah pada Pembelajaran Matematika dalam Jaringan - Inggita Nurjanah; Fitri Alyani (Jurnal Elemen, 2021)
Mathematics anxiety of high school students in learning mathematics in the network has a lot of influence on the ongoing learning until the results obtained. The influence of math anxiety has an effect ranging from understanding mathematical concepts to student learning outcomes. This study aims to determine the level of anxiety experienced by students in undergoing online learning and determine the bias between respondents and statements on the questionnaire. This research was conducted through a combined approach of quantitative and qualitative using a survey method. The subjects of this research are students with a range of secondary education who are undergoing online learning and totaling 225 students with 155 female students and 70 male students. Data was collected through the distribution of an instrument in a questionnaire regarding students' mathematics anxiety. Furthermore, the data obtained is measured through the Rasch model and processed with the help of the Winsteps application. After the data was obtained, interviews were conducted to determine the causes that support students' mathematical anxiety in the online learning system. In this study, the results obtained that anxiety tends to be high in the implementation of learning in the network. There are three categories: high anxiety 17.33%, moderate anxiety 73.78 %, and low anxiety 8.89%. This study also found various triggers for the presence of mathematical anxiety that can be used to understand the condition of students. Through DIF (Differential Item Functioning), some differences/biases can be used as references for further research.